Interjection (Racine) - Franc Schuerewegen (Carnets)
This is an analysis of the frequent use of the interjection « Hélas! » in Bérénice by Racine. The idea is that the effect is intentional (intentio auctoris). Racine has deliberately multiplied the « Hélas! » to obtain a certain effect, to explore the essence of the tragic discourse.